Improving Office Transaction in BCD Company in Quezon City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Courier services provide express and door-to-door delivery, which is fast and convenient for customers. Many businesses rely on courier services to outsource product deliveries and meet deadlines. The role of courier service providers is essential to ensure the smooth functioning of a business. This particular Courier Company has a filing department that handles office transactions such as collecting documents from departments, developing an effective document storage and filing system, and digitizing hard copies of documents. However, the researchers observed that the department staff needed help locating documents, following up on documents, and determining parcel weight and dimensions, which affected product shipments. To improve this process, the researchers proposed several procedures, including arranging documents by voucher numbers, digitalizing documents, providing extra copies of documents, creating a file for copies, dimension and weight scanning of parcels, filtering parcels by size, using Cash on Delivery (COD) for payment, reviewing transactions, and notifying clients to verify that the letter has been addressed. The researchers conducted a qualitative descriptive study, interviewing an employee of the BCD Company who needed help in this department. The employee agreed with most of the proposed procedures, believing they would be helpful and advantageous to the office procedure of the BCD company in the future and improve office transactions. The researchers recommend using technology to sort parcels and deliver them to customers with satisfaction and additional copies of documents to reduce future problems. They also suggest better documentation for transactions, compiling all important information, arranging it by voucher number for easy access, and making it more organized.
Keywords: Courier service; Filing; Delivery; Staff; Parcels